Television Programmes on Fisheries and Aquaculture: A Descriptive Study - Ghosh, Amitava; Sharma, Arpita (Indian Journal of Marketing, 2014)
Television is an effective medium for communication on which Krishi Darshan has been telecasting agriculture, animal husbandry, fisheries, and aquaculture based programmes since 2004 in West Bengal. In this context, a descriptive study of fisheries and aquaculture based television programmes telecasted on Krishi Darshan in West Bengal from 2008-2012 was performed by using content analysis approach to gain insights into and to analyze different topics of fisheries based programmes along with sector-specific programmes of agriculture, animal husbandry, and fisheries to make a valid comparison. Secondary data was accessed from the telecast register of Krishi Darshan. Sector-specific classification of programmes, namely agriculture, animal husbandry, and fisheries was also performed. Content analysis revealed that majority of the programmes were related to agriculture (83.13%) followed by animal husbandry (8.48%) and fisheries (8.39%). In case of fisheries, the majority of the topics were related to fish breeding, seed production, and hatchery management (28.72%) followed by general fisheries based topics, scientific aquaculture practices (20.21%), and brackish water aquaculture (11.70%). ANOVA showed that there was a significant difference with respect to agriculture, animal husbandry, and fisheries based programmes, and no significant difference was observed with regards to the number of different fisheries based programmes across the years. It is clear that fisheries based programmes are few in relation to other sectors. It is suggested that there is a need to increase focus on fisheries as it is a sunrise sector, and also because of its importance on our economy as well as on the livelihood, employment, and nutrition of the people of our country.